A liabilities approach to the likelihood of liquidation in business rescue. (2nd January 2018) - Rosslyn-Smith, Wesley; Pretorius, Marius
Abstract : While reorganisation procedures aim to salvage financially distressed firms, they are often abused, as uneconomic, failing firms commence with proceedings that erode value rather than preserve it. The commencement standard for business rescue is aimed at preventing such abuse, though it is often hampered by vagueness and limited practical application. Drawing on turnaround literature and the requirements of a commencement standard, this study attempts to address these drawbacks by assessing the prospect of reorganisation on commencement. The study identifies from the turnaround literature nine liabilities that could prove fatal. Under the widely-held principle of value maximisation, the researchers then propose a 'likelihood of liquidation' framework to evaluate, before the commencement of proceedings, the reasonable prospect of the firm's recovering. The analysis in this paper sets the agenda for future research and provides an opportunity to explore the practical application of the framework.